Gendered relations? Associations between Swedish parents, siblings, and adolescents' time spent sedentary and physically active - Hoy, Sara; Larsson, Håkan; Kjellenberg, Karin; Nyberg, Gisela; Ekblom, Örjan; Helgadóttir, Björg (Frontiers in Sports and Active Living, 2024)
Introduction The family is assumed to be fundamental in youth socialization processes and development, connected to social and cultural practices such as healthy lifestyles and physical activity. However, gender patterns in physical activity among adolescents and the structural drivers of gender inequality (e.g., parentage and siblingship) are poorly understood. The aim of this study was to explore further how gender structures relate to adolescents' time spent being sedentary and physically active, using contemporary gender theory. Methods This cross-sectional study involved 1,139 adolescents aged 13-14 and their parents, including 815 mothers and 572 fathers. Physical activity and time spent sedentary were assessed through accelerometry among adolescents and through a self-report questionnaire for parents validated against accelerometry. Results The results showed significant relationships between mothers' moderate-to-vigorous physical activity (MVPA) and girls' MVPA on weekdays and weekends, and fathers' MVPA was significantly related to girls' MVPA on weekdays. Our results imply that the relationship between Swedish parents' and adolescent girls' physical activity in higher intensities are to some extent gendered practices. However, time spent sedentary does not seem to show any patterns of being performed according to binary ideas of gender. Further, our exploratory analyses suggest that these results somewhat intersect with parents' educational level and relate to intra-categorical aspects of doing gender. The results also indicate slight gendered patterns in the “doing” of brotherhood for time spent sedentary, however, for boys only on weekends. Discussion The study contributes to the understanding of gender norms as constraints and enablers for adolescents' participation in physical activity. The results can spur public health and physical activity research to apply a contemporary gender theory approach, and to expand the research agenda connected to what relates to gender inequalities in physical activity practices.